Analysis of Postpartum Blues In Partworld Mothers In The Working Area of The Kedaung Barat Health Center, Tangerang District, 2023 - Vivi Silawati; Dina Nurdiana (International Journal of Midwifery and Health Sciences, 2024)
Postpartum Blues is influenced by age, education, parity, type of delivery, physical fatigue, husband's support, and family support. This research aims to determine the factors associated with the incidence of postpartum blues in the Kedaung Barat Health Center Working Area, Tangerang Regency in 2023. This research design uses a cross-sectional quantitative descriptive approach. Research respondents The population in this study was parturient mothers in the West Kedaung Health Center Working Area, Tangerang Regency, in October-December 2023, totaling 183 people. The sampling technique used is proportional sampling. The results of the research showed that the frequency distribution of postpartum blues was 20%, the age of postpartum mothers who were not at risk was 20-35 years, 65.7%, mothers with low education were 77.1%, multiparous mothers were 57.1%, and the type of birth was normal. 82.9%, 61.4% of postpartum mothers experienced physical fatigue, 57.1% of mothers did not receive husband support, and 58.6% of mothers did not receive family support. Postpartum mothers need to know information about postpartum blues so that mothers can prevent or overcome the occurrence of postpartum blues.